The effectiveness of the process approach in the development of scientific attitudes and in the acquisition of concepts in high school science 1. IN Thesis abstracts [column] - Campomanes, Elisa P. (Leyte-Samar Studies, 1987)
The process approach is one of the current trends in science teaching both in the elementary and in the secondary level. It was conceived with the idea that science is not an organized body of knowledge. Rather, it is a process, a way of arriving at some end products, or an increase in knowledge. The use of the process approach in science teaching started in the United States in the early part of the 1960's. In the Philippines, it started in the early part of 1970's. From then on, teachers' pre-service and in-service trainings have been geared towards improving teachers' skills and competence in teaching science using this approach. During the early stage of its implementation both here in our country and abroad, some studies were conducted on its effectiveness in science teaching. There were also some studies which tried to determine the teachers' as well as the student's preparedness for such an approach. In another sense, the process approach became a popular topic for research.